Is Personality Endogenous? Evidence from Ireland - Irene Mosca; Robert E. Wright (Institute of Labor Economics (IZA), 2018)
There is a growing interest in economics in the role played by personality in explaining labour market behaviour. Research to date points to the Big-5 personality traits being a possible determinant of wages and employment. However, most of this research is based on the assumption that personality is exogenous. This paper examines the potential endogeneity of personality in the context of employment behaviour amongst Irish women. A quasi-experimental design, generated by implementation and abolition of the so-called "Marriage Bar", is employed. The Marriage Bar was the legal requirement that women leave paid employment upon getting married in Ireland. Because this law was abolished only in the 1970s, many of the women affected are still alive and are among the respondents in The Irish Longitudinal Study on Ageing. The identification strategy is based on the comparison of two groups of women affected by the Marriage Bar. The comparison is between those who returned to employment after being forced to leave the labour market and those who did not. The analysis supports the view that researchers interested in the relationship between the Big-5 and labour market outcomes should not view the potential problem of "the endogeneity of personality" as a problem.
Keywords: J2; J4; J7; 330; Big-5 personality traits; labour market success; endogeneity; discrimination